Lean six sigma for hospitals : simple steps to fast, affordable, and flawless healthcare - Arthur, Jay, 1951- (New York : McGraw-Hill, 2011)
'Lean Six Sigma for Hospitals explains how to use tested LSS methods and tools to achieve the goals of better, faster, and cheaper healthcare. These strategies follow the patient from the front door of the hospital or emergency room all the way through discharge, examining key aspects of patient flow and quality and also follow the trail of billing and collections to discover major leaks in cash flow. The book emphasizes both the clinical and operational sides, so the'three demons of healthcare': delay, defects, and deviation, can be reduced'--Provided by publisher.
Bibliographical : p. 333-336.
Keywords: Hospitals -- Administration; Organizational effectiveness; Medical care -- Quality control; Total quality management; Hospital Administration -- methods; Efficiency, Organizational; Quality of Health Care -- organization & administration; Total Quality Management -- methods